Development of New Isolation and Quantification Method of Piperine from White Pepper Seeds (Piper Nigrum L) Using A Validated HPLC - Nindya Kusumorini; Akhmad Kharis Nugroho; Suwijiyo Pramono; Ronny Martien (Universitas Gadjah Mada, 2021)
Most of the active pharmaceutical ingredients in the pharmaceutical world are obtained from natural ingredients, one of which is white pepper. White pepper seeds (Piper nigrum L.) contain the main alkaloid compound piperine, which has a broad spectrum pharmacological effect. This research aimed to isolate the piperine compound from white pepper seeds to make piperine more economical, simple, and effective so that it can be applied to large scale production in the pharmaceutical industry. The method of extracting and purifying piperine compounds was carried out using n-hexane and cyclohexane. The results of the isolated piperine were tested for their purity with a set of melting point apparatus, bidimensional TLC, and HPLC. The structure compound was then analyzed using FTIR and NMR. Furthermore, the isolated piperine was tested for its antioxidant activities using DPPH, ABTS, and FRAP. Cyclohexane was successfully used to remove the resinous matter from the n-hexane extract of white pepper to produce isolated piperine with 97.24% of purity. The results of the melting point, FTIR, 1H-NMR, and 12C-NMR of the isolated piperine were similar to that of the piperine reference substance and the literature review. The isolated piperine has weak antioxidant activities in the ABTS and FRAP test with the results of 15.25 ± 0.004 mM and 10.53 mol TE/g of the sample, respectively.